Rapid in-air ultrasound holography measurement and camera-in-the-loop generation using thermography - Zak Morgan; Youngjun Cho; Sriram Subramanian (Communications Engineering)
Abstract Ultrasound holography, pivotal in applications like mid-air haptics, volumetric displays and 3D printing, faces challenges in the crafting and timely measurement of precise acoustic holograms. Current methods, bench-marked via simulations due to slow measurement times, often neglect real-world complexities such as non-linearity and hardware tolerances, leading to discrepancies between predicted and observed results. Here we introduce a real-time 2D thermographic measurement technique orders of magnitude faster than microphone scans, although with reduced accuracy and no phase information, with a maximum peak pressure of 4.25 kPa validated and a demonstrated average accuracy of 2.5% in peak measurement. Higher pressures of approximately 12 kpa were captured, but validation was limited by the microphone. This method is grounded in thermo-viscous acoustic models for thin-ducts and micro-perforated plates. Finally, we integrate this with holography algorithms to propose a camera-in-the-loop algorithm that employs real-time measurement, enabling targeted data acquisition and on-line training of acoustic holography algorithms. This method achieved a 1.7% error in pressure with a single point compared to 7.8% for a conventional algorithm, and a 3.6% error and 4.2% standard deviation for 16 points compared to 9.7% and 6.9%. We further envisage this method as being capable of measuring acoustic streaming.